2018
DOI: 10.1177/0033294118813844
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Expanded Version of the Inventory of Depression and Anxiety Symptoms in a Turkish Population

Abstract: The study examined psychometric properties of the Turkish version of the Inventory of Depression and Anxiety Symptoms-II (IDAS-II) in a Turkish sample. The sample consisted of nonclinical ( N = 931) and clinical ( N = 208) individuals. Confirmatory factor analysis showed that Turkish IDAS-II was similar to the original IDAS-II and supported the construct validity of the test. The Turkish IDAS-II showed good internal consistency, significant acceptable retest correlations, and was sensitive to changes over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(57 citation statements)
references
References 54 publications
12
33
0
Order By: Relevance
“…Internal consistency was high (i.e., 𝜔 > .8) for all scales except Euphoria and Ordering. Concerning Euphoria, similar results were obtained using the original IDAS-II and its existing translations (De la Rosa-Cáceres et al, 2020;Irak & Albayrak, 2020;Watson et al, 2012). This lower internal consistency might be due to the fact that Euphoria, as a symptom dimension of bipolar disorder, is broader than other scales and contains items tapping into elevated mood (e.g., "I felt elated for no special reason"), heightened energy (e.g., "I had so much energy it was hard for me to sit still"), and grandiosity (e.g., "I felt that I could do things that other people couldn't").…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Internal consistency was high (i.e., 𝜔 > .8) for all scales except Euphoria and Ordering. Concerning Euphoria, similar results were obtained using the original IDAS-II and its existing translations (De la Rosa-Cáceres et al, 2020;Irak & Albayrak, 2020;Watson et al, 2012). This lower internal consistency might be due to the fact that Euphoria, as a symptom dimension of bipolar disorder, is broader than other scales and contains items tapping into elevated mood (e.g., "I felt elated for no special reason"), heightened energy (e.g., "I had so much energy it was hard for me to sit still"), and grandiosity (e.g., "I felt that I could do things that other people couldn't").…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, Stasik-O'Brien et al (2019) showed that IDAS-II scales are good predictors of their associated DSM-IV as well as DSM-5 diagnoses and provided cut-off scores for different uses. Recently, Turkish (Irak & Albayrak, 2020) and Spanish (De la Rosa-Cáceres et al, 2020) versions of the IDAS-II have been developed and shown to exhibit similar psychometric properties as the original version.…”
Section: Inventory Of Depression and Anxiety Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Turkish validity and reliability studies were performed by Irak. The Turkish IDAS-II subscales revealed Cronbach's alpha values ranged between 0.947 and 0.949 and the items have a relatively high internal consistency [11].…”
Section: Clinical Measuresmentioning
confidence: 99%
“…Beck Anxiety Inventory and the Beck Depression Inventory were applied to the patients at the discretion of the paediatric psychiatrist. 11,12 After a detailed clinical evaluation, patients without any causes to explain chest pain were considered as idiopathic.…”
Section: Diagnostic Categoriesmentioning
confidence: 99%